Efficient enhancement on crystallization and electrochemical performance of LiMn2O4 by recalcination treatment. Issue 12 (December 2022) - Hao, Jiabin; Hao, Siqi; Xie, Mu
Abstract: Spinel LiMn2 O4 cathode material was obtained by a recalcination treatment, which exhibits excellent crystallization and electrochemical performance. A series of test and analysis results revealed that the performance enhancement of as-prepared sample is related to the crystal structure, morphology and electrochemical properties. Owing to the recalcination treatment, the spinel LiMn2 O4 presents a truncated-octahedral morphology with selective growth of the (110) and (100) crystal planes, which would effectively inhibit manganese dissolution. Moreover, the optimized sample exhibits a better crystallinity and electrochemical reversibility than that of pristine sample, which can provide a faster Li ion de-intercalation/intercalation kinetics. Hence, the spinel LiMn2 O4 cathode material delivers a high initial discharge capacity of 112.3 mAh·g −1 with a good capacity retention of 90.3% after 500 cycles and an excellent rate performance. This study constructed a facile and meaningful method to prepare spinel LiMn2 O4 cathode material, which may facilitate the development of lithium-ion batteries. Highlights: The spinel R-LMO cathode material was successfully prepared by recalcination treatment process. The R-LMO present the selective growth of the (110) and (100) crystal planes. The R-LMO displays the better electrochemical performance than that of P-LMO. Abstract : Energy storage and conversion; Crystal growth; Lithium-ion batteries; Spinel LiMn2 O4 ; Recalcination treatment.